Implementing non-equilibrium networks with active circuits of duplex catalysts - Lankinen,A; Ruiz,IM; Ouldridge,TE (Schloss Dagstuhl--Leibniz-Zentrum, 2020)
DNA strand displacement (DSD) reactions have been used to construct chemicalreaction networks in which species act catalytically at the level of theoverall stoichiometry of reactions. These effective catalytic reactions aretypically realised through one or more of the following: many-stranded gatecomplexes to coordinate the catalysis, indirect interaction between thecatalyst and its substrate, and the recovery of a distinct ``catalyst'' strandfrom the one that triggered the reaction. These facts make emulation of theout-of-equilibrium catalytic circuitry of living cells more difficult. Here, wepropose a new framework for constructing catalytic DSD networks: ActiveCircuits of Duplex Catalysts (ACDC). ACDC components are all double-strandedcomplexes, with reactions occurring through 4-way strand exchange. Catalystsdirectly bind to their substrates, and and the ``identity'' strand of thecatalyst recovered at the end of a reaction is the same molecule as the onethat initiated it. We analyse the capability of the framework to implementcatalytic circuits analogous to phosphorylation networks in living cells. Wealso propose two methods of systematically introducing mismatches within DNAstrands to avoid leak reactions and introduce driving through net base pairformation. We then combine these results into a compiler to automate theprocess of designing DNA strands that realise any catalytic network allowed byour framework.